Need for hydro storage due to the challenges arising from expansion of PV electricity generation - Marija Lazarevikj, Darko Babunski, Viktor Iliev and Zoran Markov (My University, 2025)
Hydropower has a crucial role in the clean energy transition (CET) due to the low-carbon electricity production, the sustainability, reliability and flexibility it provides. Both the fast response and storage potential make hydropower a basis for integrating wind and solar power whose output vary depending on external conditions. Many European countries have considerable remained feasible potential for hydropower development, among which is North Macedonia (MK). As a member of the Energy Community, MK aligns with European energy policies by adopting and implementing EU energy directives and regulations. The energy scenarios illustrate the country's energy transition, forecasting its reaction to EU policies and government efforts aimed at achieving a net-zero economy by 2050. However, the country's cost-competitive potential is constrained by factors like low wind speeds and inaccessible terrain in certain regions, making photovoltaics (PV) the fastest growing renewable energy source (RES) technology. Thus, the electricity production from PVs in North Macedonia experiences exponential growth throughout the last four years. The challenges arising from PV expansion are imposing the need for improvement of the energy system flexibility to accommodate the new and highly fluctuating demands. Hence, hydropower could play a major role as dispatchable power source to back up variable PV and balance variations from PV generation. Due to this, the current state of RES capacity and generated electricity with focus on hydropower in MK has been analysed in this paper. Subsequently, an investigation of the possibilities for increasing the electricity production from hydropower to add flexibility to the power system in MK is performed and finally the related challenges have been presented. The steps towards higher flexibility of the energy system in North Macedonia are analysed including usage of existing hydropower plants (HPPs), but also construction of new storage HPPs and pumped storage HPPs for peak demand management and avoiding blackouts under critical circumstances. Some of the existing HPPs can be upgraded through equipment refurbishment and storage increase to gain flexibility. Due to being a technology able to address the flexibility challenges posed by the rise in photovoltaic (PV) installations, pumped storage hydropower was also recognised as a possibility. According to the energy strategy, construction of both large and small HPPs based on the remaining technically and economically feasible potential is envisaged. Small HPPs are prioritized due to their technical feasibility and lower investments. Financial support mechanisms are introduced to stimulate small HPPs and construction conditions are already established for some of them, however, an adjustment in accordance with the administrative requirements in certain areas is needed to ensure environmental sustainability. Moreover, integrating innovative technologies into hydropower can significantly enhance the energy transition at the national level, particularly by improving efficiency, flexibility, and environmental sustainability. Various challenges related to environmental protection, lifetime and maintenance of HPPs components so as economical limitations are being discussed.
Keywords: Flexibility, Storage, Pumped hydro, PV